Burden and seasonality of primary and secondary symptomatic common cold coronavirus infections in Nicaraguan children. Issue 1 (9th December 2022) - Frutos, Aaron M.; Balmaseda, Angel; Vydiswaran, Nivea; Patel, Mayuri; Ojeda, Sergio; Brouwer, Andrew; Tutino, Rebecca; Cai, Shuwei; Bakker, Kevin; Sanchez, Nery; Lopez, Roger; Kuan, Guillermina; et al.
Abstract: Background: The current SARS‐CoV‐2 pandemic highlights the need for an increased understanding of coronavirus epidemiology. In a pediatric cohort in Nicaragua, we evaluate the seasonality and burden of common cold coronavirus (ccCoV) infection and evaluate likelihood of symptoms in reinfections. Methods: Children presenting with symptoms of respiratory illness were tested for each of the four ccCoVs (NL63, 229E, OC43, and HKU1). Annual blood samples collected before ccCoV infection were tested for antibodies against each ccCoV. Seasonality was evaluated using wavelet and generalized additive model (GAM) analyses, and age–period effects were investigated using a Poisson model. We also evaluate the risk of symptom presentation between primary and secondary infections. Results: In our cohort of 2576 children from 2011 to 2016, we observed 595 ccCoV infections and 107 cases of ccCoV‐associated lower respiratory infection (LRI). The overall incidence rate was 61.1 per 1000 person years (95% confidence interval (CI): 56.3, 66.2). Children under two had the highest incidence of ccCoV infections and associated LRI. ccCoV incidence rapidly decreases until about age 6. Each ccCoV circulated throughout the year and demonstrated annual periodicity. Peaks of NL63 typically occurred 3 months before 229E peaks and 6 months after OC43 peaks. Approximately 69% of symptomatic ccCoV infections were secondary infections. There was slightly lower risk (rate ratio (RR): 0.90, 95% CI: 0.83, 0.97) of LRI between secondary and primary ccCoV infections among participants under the age of 5. Conclusions: ccCoV spreads annually among children with the greatest burden among ages 0–1. Reinfection is common; prior infection is associated with slight protection against LRI among the youngest children.